Shapes and Their Equations: Experimentation with Desmos - Iobst, Christopher Simon (Ohio Journal of School Mathematics, 2018)
The author explores common polygons—squares, triangles, trapezoids—and uses the free online grapher, Desmos, to derive single equations that generate the shapes. Throughout, the author discribes his inquiry-based approaches—the trials and errors he employs in his eventual discovery of various shape-generating equations.